PENGARUH KEBIJAKAN REVERSE STOCK SPLIT TERHADAP VOLUME PERDAGANGAN SAHAM PERUSAHAANGO PUBLIC YANG TERDAFTAR DALAMBURSA EFEK INDONESIA TAHUN 2003 – 2013 - Ahmad Fahmi; Wiriadi Sutrisno; Pardiono Pardiono (JABE (Journal of Applied Business and Economic), 2016)
The aim of the research is to find empirical evidence whether the reverse stock split policies have a significant impact on the stock volume in companies that conduct the policy. This study uses event study approach, which made observations on the activity of trading volume during  ten (10) days before,on that 10 (ten) days  and  the  10 days after reverse stock split policy. The sample used in this study were 16 (sixteen) company of 31 companies which perform a reverse stock split policy for the years 2003 u to 2013. The hypothesis examine using parametric inferential statistics  that  through the Wilcoxon signed test rangks test such  the data are not normally distributed. The results of this study showed that the difference between the average trading volume activity before and after the reverse stock split policy is  statistically significant, where the probability value (0.023) is smaller than the significance level (?) = 5% or 0.05, so the hypothesis (Ha ) which states there is a significant difference between the average trading volume activity before and after the  reverse stock split acceptable policy. That is the reverse stock split policies have a significant impact on the company's stock trading volume.